Penegakan Hukum terhadap Mafia Karantina COVID-19 Sebagai Pelanggar Undang-Undang Kekarantinaan dan Pelaku Tindak Pidana Pemalsuan - Zul Afiatul Kharisma; Kristiani Virgi Kusuma Putri (CV Rewang Rencang, 2021)
Positive cases of COVID-19 in Indonesia are increasing significantly. In dealing with this, the government has implemented various policies, one of which is regarding the COVID-19 quarantine, which is based on Law Number 6 of 2018 concerning Health Quarantine. However, in fact, there are still violations in its implementation. Like the case of the COVID-19 quarantine mafia that occurred at Soekarno Hatta Airport. From the results of the research, the perpetrators are suspected of having violated the Quarantine Law and committed a criminal act of forgery, as well as the inaccuracy of law enforcement officers in ensnaring the perpetrators. So that the sanctions that will be imposed are also fairly light and unfair, especially if we observe the impact of it.